(untitled) (Modern American Journal of Social Sciences and Humanities, 2026)
This article examines the step-by-step formation of physical training in young gymnasts as an essential condition for effective sports development, safe motor learning, and long-term athletic progress. Gymnastics requires a high level of flexibility, strength, coordination, balance, speed, endurance, rhythm, spatial orientation, and psychological stability. However, these qualities cannot be developed chaotically or only through intensive repetition. They must be formed gradually, according to the age, functional readiness, individual abilities, and biological development of young athletes. The article emphasizes that the training process in childhood should be based on pedagogical consistency, progressive load distribution, technical accuracy, safety, motivation, and the harmonious development of the body. Special attention is given to the importance of general physical preparation at the initial stage, gradual transition to special physical preparation, and the integration of physical qualities with technical elements. The study also highlights the role of the coach as a pedagogical organizer who creates conditions for the child’s physical, emotional, and motor development. A scientifically grounded step-by-step approach makes it possible to prevent overload, reduce injury risks, improve movement culture, and prepare young gymnasts for more complex technical tasks. The article is intended for specialists in physical education, sports pedagogy, gymnastics coaching, and students of pedagogical universities specializing in sports.